2022
DOI: 10.3390/ijms23105615
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Molecular Mechanisms of Nitric Oxide-Induced Low-Temperature Tolerance in Cucumber by Transcriptome Profiling

Abstract: Cucumber (Cucumis sativus L.) is one of the most popular cultivated vegetable crops but it is intrinsically sensitive to cold stress due to its thermophilic nature. To explore the molecular mechanism of plant response to low temperature (LT) and the mitigation effect of exogenous nitric oxide (NO) on LT stress in cucumber, transcriptome changes in cucumber leaves were compared. The results showed that LT stress regulated the transcript level of genes related to the cell cycle, photosynthesis, flavonoid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Knockdown of five genes of Lhcb1 in Arabidopsis resulted in chlorophyll loss and delayed growth 55 . Down-regulation of Lhcb1 , Lhcb3 and Lhcb5 genes expression levels in cucumber affected its photosynthesis 56 . In contrast, significant up-regulation of the five Lhcb1 genes during embryogenesis might contribute to their light capture and photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of five genes of Lhcb1 in Arabidopsis resulted in chlorophyll loss and delayed growth 55 . Down-regulation of Lhcb1 , Lhcb3 and Lhcb5 genes expression levels in cucumber affected its photosynthesis 56 . In contrast, significant up-regulation of the five Lhcb1 genes during embryogenesis might contribute to their light capture and photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptomics has become an essential tool for deciphering the molecular mechanisms underlying disease resistance in cucumber. Wu [ 45 ] used transcriptomic sequencing to examine the expression profiles of cucumber plants grown under low-temperature conditions. They found that low-temperature stress regulated the transcript levels of genes related to phenylalanine metabolism, the phytohormone ethylene, photosynthesis, flavonoid accumulation, lignin synthesis, cells, cycleactive gibberellin, and salicylic acid (SA) signaling in cucumber seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis identified 285 and 839 DEGs in chilling-tolerant (CC) and chilling-susceptible (R1461) cucumber cultivars, respectively ( Tables S3 and S4 ), suggesting that these genes may confer chilling tolerance in cucumber. GO analysis was used to analyze the functions of plant genes in response to low-temperature stress [ 5 , 27 , 28 , 35 , 39 ]. Previous studies found that chilling induces ethylene production in cucumber [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis has been identified as an efficient experimental tool to investigate the genome functions and physiological regulation mechanisms of chilling stress [ 26 , 27 , 28 ]. Recently, physiological and transcriptome analysis has indicated that the interactions between auxin and hydrogen sulfide signaling are involved in cucumber chilling tolerance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation